PENGARUH RESIKO KREDIT DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Syamsuddin, M. Syamsunil; Haeril; Nirmasari, Dian (Paser Institute Of Accounting and Finance, 2024)
Credit risk and liquidity are factors that can influence the performance of banking companies, especially profitability indicators, because these two variables can have a big impact on the profits obtained by banks in a certain period. So the aim of this research is to find out how much influence Credit Risk and Liquidity have on Banking Companies listed on the Indonesia Stock Exchange (BEI). The research method used was quantitative method with an associative correlation approach to find the influence relationship among variables. The source of this research came from financial reports through documentation techniques. The population in this study were 42 banking companies listed on the Indonesia Stock Exchange, while the sampling technique used was Purposive Sampling so that the sample obtained were 7 companies that based on the criteria. The data analysis method used was multiple linear analysis. The results of this research showed that partially Credit Risk had a negative and significant influence on Profitability, Liquidity had no significant influence on Profitability. Then simultaneously Credit Risk and Liquidity had a positive and significant influence on Profitability.